MoM total hip replacements in Europe: a NORE report - Pijls BG; Meessen JMTA; Tucker K; Stea S; Steenbergen L; Fenstad AM; Mäkelä K; Stoica IC; Goncharov M; Overgaard S; de la Torre JA; Lubbeke A; et al. (BRITISH EDITORIAL SOC BONE & JOINT SURGERY, 2022)
The purpose of this paper is to determine the prevalence of metal-on-metal (MoM) total hip replacement (THR) in European registries, to assess the incidence of revision surgery and to describe the national follow-up guidelines for patients with MoM THR including resurfacings.Eleven registries of the Network of Orthopaedic Registries of Europe (NORE) participated totalling 54 434 resurfacings and 58 498 large stemmed MoM THRs.The resurfacings and stemmed large head MoM had higher pooled revision rates at five years than the standard total hip arthroplasties (THA): 6.0%, 95% confidence interval (CI) 5.3 to 6.8 for resurfacings; 6.9%, 95% CI 4.4 to 9.4 for stemmed large head MoM; and 3.0%, 95% CI 2.5 to 3.6 for conventional THA.The resurfacings and stemmed large head MoM had higher pooled revision rates at ten years than the standard THAs: 12.1%, 95% CI 11.0 to 13.3 for resurfacings; 15.5%, 95% CI 9.0 to 22 for stemmed large head MoM; and 5.1%, 95% CI 3.8 to 6.4 for conventional THA.Although every national registry reports slightly different protocols for follow-up, these mostly consist of annual assessments of cobalt and chromium levels in blood and MRI (MARS) imaging.